La imagen tricontinental La Feminidad, el Che Guevara y el Imperialismo a través del arte gráfico de la OSPAAAL - García Molinero, Alberto (Biblioteca Historia de América, 2022)
The existing studies and lines of research around the Solidarity Organization of the Peoples of Asia, Africa and Latin America and the Tricontinental design are relatively recent in the field of history. There is no work that has delved into the materials collected within the more than one hundred and eighty-four issues published by the Tricontinental magazine to date. This study, which delves into the history of the organization and into the analysis of three specific representational models of Tricontinental graphic art, aspires to offer new interpretive keys around the Femininity of the Global South, the image of Ernesto Che Guevara and the Imperialism from an alternative point of view scarcely worked until now in the field of historical research.